Hydrogel as well as preparation method and application thereof

Through photocrosslinking and salting treatment, hydrogels with high strength and good resistance to extreme conditions were prepared, which solved the problem of insufficient performance of traditional hydrogels under extreme conditions and achieved effective application of flexible sensors in various environments.

CN119823326APending Publication Date: 2025-04-15GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510028959.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Conventional hydrogel materials exhibit limited performance under extreme conditions of freezing and underwater, limiting the application range of flexible sensors prepared from hydrogels.

Method used

By mixing polyvinyl alcohol, 2-acrylamide-2-methylpropanesulfonic acid, strong alkali, photoinitiator, crosslinking agent and water, photocrosslinking and cyclic freeze-thawing, salting out, hydrogel with high strength, elongation of break and toughness, and good anti-freeze and swelling resistance.

Benefits of technology

The prepared hydrogel has high tensile strength, elongation at break and toughness, and can be used in a variety of environments. It is suitable for the preparation of flexible sensors worn in various parts of the human body to achieve long-term monitoring of the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823326A_ABST
    Figure CN119823326A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogel materials, and particularly relates to hydrogel as well as a preparation method and application thereof. The preparation method of the hydrogel provided by the invention comprises the following steps: mixing polyvinyl alcohol, 2-acrylamide-2-methylpropanesulfonic acid, strong alkali, a photoinitiator, a cross-linking agent and water, and carrying out photo-crosslinking to obtain pre-gel; the pre-gel is circularly frozen and thawed and then salted out, and the hydrogel material is obtained. The hydrogel prepared according to the preparation method disclosed by the invention has relatively high strength, elongation at break and toughness and has good anti-freezing and anti-swelling properties, and a flexible sensor prepared from the hydrogel can be used in various environments and can better realize long-time monitoring on a human body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical hydrogel materials, and in particular relates to a hydrogel and a preparation method and application thereof. Background Art

[0002] Cardiovascular disease has always been a high-risk disease in the world. It covers many abnormal conditions in the heart and vascular system. The morbidity and mortality rates continue to increase, causing great harm to human health. There are many causes of cardiovascular disease. In addition to congenital genetic factors, bad living habits and excessive strenuous exercise (such as swimming) can trigger a series of pathological reactions. In order to reduce the risk of disease, advance knowledge is an important means, among which monitoring is a means with important prompting significance. However, the traditional monitoring equipment is bulky and not conducive to the monitoring of various parts of the human body. In order to achieve the monitoring of various parts of the human body, researchers have proposed wearable flexible sensors for the human body. Flexible sensors are small in size and have good fit to the human body. In recent years, hydrogel has become one of the commonly used materials for preparing wearable flexible sensors for the human body. Hydrogel can contact human skin well, which is conducive to the accuracy of signal acquisition. However, traditional hydrogel materials have disadvantages such as being limited by extreme conditions such as freezing and underwater, which limits the application scope of flexible sensors prepared by hydrogels. Summary of the invention

[0003] In view of this, the present invention provides a hydrogel and a preparation method and application thereof. The hydrogel obtained according to the preparation method provided by the present invention has high strength, elongation at break and toughness, and has good anti-freezing and anti-swelling properties. The flexible sensor prepared using the hydrogel can be used in a variety of environments.

[0004] In order to solve the above technical problems, the present invention provides a method for preparing a hydrogel, comprising the following steps:

[0005] Mixing polyvinyl alcohol, 2-acrylamide-2-methylpropane sulfonic acid, a strong base, a photoinitiator, a crosslinking agent and water, and performing photocrosslinking to obtain a pregel;

[0006] The pregel is freeze-thawed cyclically and then salted out to obtain the hydrogel.

[0007] Preferably, the mixing comprises the following steps:

[0008] first mixing the polyvinyl alcohol and a portion of water to obtain a polyvinyl alcohol aqueous solution;

[0009] First dissolving a strong base in the remaining portion of water to obtain a strong base solution;

[0010] dissolving the 2-acrylamide-2-methylpropanesulfonic acid in the polyvinyl alcohol aqueous solution to obtain a first mixed solution;

[0011] The first mixed solution and the strong base solution are mixed for a second time to obtain a second mixed solution;

[0012] The second mixed solution, the photoinitiator and the cross-linking agent are mixed for the third time.

[0013] Preferably, the mass ratio of the polyvinyl alcohol to part of the water is 1:8-9; the temperature of the first mixing is 95-105° C., and the time of the first mixing is 40-60 min;

[0014] The strong base includes sodium hydroxide or potassium hydroxide; the mass ratio of the strong base to the remaining water is 2:4-7;

[0015] The mass ratio of the polyvinyl alcohol aqueous solution to 2-acrylamide-2-methylpropane sulfonic acid is 5:0.6-0.9; the temperature of the second dissolution is 60-65° C., the second dissolution is carried out under stirring, and the stirring time is 5-10 minutes;

[0016] The mass ratio of polyvinyl alcohol to strong base in the second mixed solution is 1:0.4-0.7.

[0017] Preferably, the photoinitiator includes 1-hydroxycyclohexyl phenyl ketone; the crosslinking agent includes polyethylene glycol diacrylate;

[0018] The mass ratio of the 2-acrylamide-2-methylpropanesulfonic acid, the photoinitiator and the crosslinking agent is 1.6: 0.015-0.016: 0.048-0.060;

[0019] The temperature of the third mixing is 60-65° C., the third mixing is performed under stirring, and the stirring time is 30-40 minutes.

[0020] Preferably, the light used for photo-crosslinking is ultraviolet light; and the time for photo-crosslinking is 35 to 45 minutes.

[0021] Preferably, the cyclic freeze-thaw is a cyclic freezing and thawing process, wherein the time for a single freezing is 11 to 13 hours, the time for a single thawing is 11 to 13 hours, and the number of cycles is 2 to 3 times.

[0022] Preferably, before the salting out, the process further comprises: soaking the product after freeze-thaw cycles in water for 11 to 13 hours;

[0023] The salting out is to soak the product after soaking in water in an inorganic salt solution;

[0024] The inorganic salt solution includes sodium chloride solution, magnesium chloride solution, calcium chloride solution or potassium chloride solution;

[0025] The molar concentration of the inorganic salt aqueous solution is 2 to 5 mol / L;

[0026] The soaking time in the inorganic salt solution is 11 to 13 hours.

[0027] The present invention also provides a hydrogel prepared by the preparation method described in the above technical scheme, wherein the tensile strength of the hydrogel is 1.2-1.44 MPa, the elongation at break is 386.49-403.8%, and the toughness is 2.09-2.79 MJ / m 3 , Young's modulus is 0.29-0.36 MPa; the swelling rate of the hydrogel after being immersed in water for 7 days is 11.67-17.87%.

[0028] The present invention also provides the use of the hydrogel described in the above technical solution as a medical material.

[0029] Preferably, the hydrogel is used as a raw material to prepare a flexible sensor.

[0030] The present invention provides a method for preparing a hydrogel, comprising the following steps: mixing polyvinyl alcohol, 2-acrylamide-2-methylpropane sulfonic acid, a strong base, a photoinitiator, a crosslinking agent and water, performing photocrosslinking to obtain a pregel; and performing salting out after freeze-thawing the pregel to obtain the hydrogel material. In the present invention, poly-2-acrylamide-2-methylpropane sulfonic acid can provide a polymer molecular chain with an acid group to form a double network structure with polyvinyl alcohol, and the interaction or mutual entanglement between the two polymer networks can improve the mechanical properties of the hydrogel. The present invention promotes the ionization of the sulfonic acid group in the acidic polymer by adding a strong base, and then uses the acid ion to induce the crystallization of polyvinyl alcohol, thereby improving the mechanical properties and anti-swelling properties of the hydrogel. The present invention penetrates the salt solution into the interior of the hydrogel through salting out, induces crystallization, and the cations in the salt solution can also interact with the polymer network to reduce the freezing point of water, thereby improving the mechanical properties of the hydrogel and giving it good anti-swelling and anti-freezing properties. The hydrogel prepared according to the preparation method of the present invention has high strength, elongation at break and toughness, and has good anti-freezing and anti-swelling properties. The flexible sensor prepared using the hydrogel can be used in a variety of environments and can better achieve long-term monitoring of the human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of the process of preparing the hydrogel according to the present invention;

[0032] Figure 2 XRD spectra of the hydrogels prepared in Examples 1 to 4 and Comparative Examples 1 to 3;

[0033] Figure 3 The swelling physical pictures of the hydrogels prepared in Example 3, Comparative Example 2 and Comparative Example 3;

[0034] Figure 4 Actual pictures of the antifreeze test of the hydrogels of Examples 1 to 4 and Comparative Examples 1 to 3;

[0035] Figure 5 The hydrogel and commercial gel electrodes of Example 3 are used to monitor the ECG of the human body under different conditions at room temperature;

[0036] Figure 6 Schematic diagram of the hydrogel and commercial gel electrode of Example 3 after being immersed in water;

[0037] Figure 7 This is the electrocardiogram monitoring of the human body under different conditions by the hydrogel in Example 3 after being soaked in water. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing a hydrogel, comprising the following steps:

[0039] Mixing polyvinyl alcohol, 2-acrylamide-2-methylpropane sulfonic acid, a strong base, a photoinitiator, a crosslinking agent and water, and performing photocrosslinking to obtain a pregel;

[0040] The pre-gel is freeze-thawed cyclically and then salted out to obtain the hydrogel material.

[0041] In the present invention, unless otherwise specified, all materials are conventional commercially available products.

[0042] The present invention mixes polyvinyl alcohol, 2-acrylamide-2-methylpropane sulfonic acid, a strong base, a photoinitiator, a crosslinking agent and water, and performs photocrosslinking to obtain a pregel. As a specific embodiment of the present invention, the mixing may include the following steps:

[0043] first mixing the polyvinyl alcohol and a portion of water to obtain a polyvinyl alcohol aqueous solution;

[0044] First dissolving a strong base in the remaining portion of water to obtain a strong base solution;

[0045] dissolving the 2-acrylamide-2-methylpropanesulfonic acid in the polyvinyl alcohol aqueous solution to obtain a first mixed solution;

[0046] The first mixed solution and the strong base solution are mixed for a second time to obtain a second mixed solution;

[0047] The second mixed solution, the photoinitiator and the cross-linking agent are mixed for the third time.

[0048] The present invention first mixes the polyvinyl alcohol and part of the water to obtain a polyvinyl alcohol aqueous solution. As a specific embodiment of the present invention, the water can be deionized water; the mass ratio of the polyvinyl alcohol (PVA) and part of the water can be 1:8-9; the temperature of the first mixing can be 95-105°C, specifically 95°C, 100°C or 105°C; the time of the first mixing can be 40-60min, specifically 40min, 45min, 50min, 55min or 60min.

[0049] The present invention first dissolves a strong base in the remaining water to obtain a strong base solution. As a specific embodiment of the present invention, the water can be deionized water, and the strong base can include sodium hydroxide or potassium hydroxide; the mass ratio of the strong base to the remaining water can be 2:4-7, and can be specifically 2:4, 2:5, 2:6 or 2:7. As a specific embodiment of the present invention, the temperature of the first dissolution can be 20-35°C, and can be specifically 20°C, 25°C, 30°C or 35°C; the first dissolution can be carried out under stirring conditions, and the stirring time can be 4-6min, and can be specifically 4min, 5min or 6min; the present invention has no special requirements for the stirring speed, as long as it can be completely dissolved.

[0050] After obtaining the polyvinyl alcohol aqueous solution, the present invention dissolves the 2-acrylamide-2-methylpropane sulfonic acid in the polyvinyl alcohol aqueous solution for the second time to obtain a first mixed solution. As a specific embodiment of the present invention, the mass ratio of the polyvinyl alcohol aqueous solution (PVA) and 2-acrylamide-2-methylpropane sulfonic acid (AMPS) can be 5:0.6-0.9, specifically 5:0.6, 5:0.7, 5:0.8 or 5:0.9; the temperature of the second dissolution can be 60-65°C; the second dissolution can be carried out under stirring, and the stirring time can be 5-10 minutes. The present invention has no special requirements for the stirring speed, as long as the dissolution is complete.

[0051] After obtaining the strong alkali solution and the first mixed solution, the present invention performs a second mixing of the first mixed solution and the strong alkali solution to obtain a second mixed solution. As a specific embodiment of the present invention, the mass ratio of polyvinyl alcohol and strong alkali in the second mixed solution can be 1:0.4-0.7, and can be specifically 1:0.4, 1:0.5, 1:0.6 or 1:0.7. As a specific embodiment of the present invention, the temperature of the second mixing can be 60-65°C; the second mixing can be carried out under stirring, and the stirring time can be 50-60 minutes. The present invention has no special requirements for the stirring speed, as long as it can be completely dissolved.

[0052] After obtaining the second mixed solution, the present invention performs a third mixing of the second mixed solution, the photoinitiator and the crosslinker. As a specific embodiment of the present invention, the photoinitiator may include 1-hydroxycyclohexyl phenyl ketone (HKCP); the crosslinker may include polyethylene glycol diacrylate (PEGDA); the mass ratio of the 2-acrylamide-2-methylpropane sulfonic acid, the photoinitiator and the crosslinker may be 1.6:0.015-0.016:0.048-0.060, or 1.6:0.0157:0.048-0.050. As a specific embodiment of the present invention, the temperature of the third mixing may be 60-65°C, the third mixing may be performed under stirring, and the stirring time is 30-40 minutes. The present invention has no special requirements for the stirring speed, as long as it can be completely dissolved.

[0053] The present invention can mix the materials evenly by performing step-by-step mixing according to the above method, and avoid the materials from agglomerating in large pieces; at the same time, the step-by-step mixing can better exert the role of each material. For example, when sodium hydroxide is added, the sodium hydroxide can promote the ionization of the sulfonic acid group, and the step-by-step mixing can reduce the influence of other materials on the ionization.

[0054] As a specific implementation of the present invention, the light used for photo-crosslinking may be ultraviolet light; the time for the photo-crosslinking may be 35 to 45 minutes, and may be specifically 35 minutes, 40 minutes or 45 minutes.

[0055] After obtaining the pre-gel, the present invention performs salting out after freeze-thawing the pre-gel in a cycle to obtain the hydrogel material. As a specific embodiment of the present invention, the freeze-thawing cycle is a cycle of freezing and thawing, and the freezing temperature can be -18 to -22°C, specifically -20°C; the single freezing time can be 11 to 13h, specifically 12h; the thawing temperature can be 8 to 12°C, specifically 10°C; the single thawing time can be 11 to 13h, specifically 12h; the number of cycles can be 2 to 3 times. The present invention can gel the polyvinyl alcohol by freezing to avoid dissolution when soaked in water later.

[0056] As a specific embodiment of the present invention, the salting out may also include: soaking the product after freeze-thaw cycle in water, the water may be deionized water, and the soaking time in water may be 11 to 13 hours, specifically 12 hours; the volume of water used for soaking in water is not particularly limited in the present invention as long as it can be immersed. The present invention soaks in water first so that a large amount of water exists inside the hydrogel and the volume expands, thereby improving the effect of subsequent inorganic salt solution penetrating into the hydrogel; at the same time, unreacted monomers, photoinitiators, and crosslinking agents can be removed by soaking in water.

[0057] As a specific embodiment of the present invention, the salting out can be soaking the product after freeze-thaw cycle or soaking in water in an inorganic salt solution; the inorganic salt solution can include sodium chloride solution, magnesium chloride solution, calcium chloride solution or potassium chloride solution; the molar concentration of the inorganic salt solution can be 2-5 mol / L, specifically 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L; the soaking time in the inorganic salt solution can be 11-13h, specifically 12h. The present invention has no special limitation on the volume of the inorganic salt solution used for soaking in the inorganic salt solution as long as it can be immersed.

[0058] Figure 1 The figure is a schematic diagram of the process of preparing the hydrogel of the present invention, specifically, dissolving 2-acrylamide-2-methylpropane sulfonic acid into a polyvinyl alcohol aqueous solution, adding sodium hydroxide and mixing evenly, and then initiating polymerization by ultraviolet light; finally, the final hydrogel product can be obtained by cyclic freeze-thaw and salting out.

[0059] In the present invention, polyvinyl alcohol can provide polymer molecular chains with hydroxyl groups, and polyvinyl alcohol is easy to obtain, easily degraded and biocompatible; poly (2-acrylamide-2-methylpropane sulfonic acid) can provide polymer molecular chains with acid groups, and can form a double network structure with the polymer molecular chains with hydroxyl groups provided by polyvinyl alcohol; this network structure can shrink, aggregate and crystallize in a salt solution; and the cations (such as sodium ions) present in the inorganic salt solution (such as sodium chloride solution) can greatly improve the electrical signal transmission performance of the hydrogel.

[0060] In the present invention, the strong base can promote the ionization of the sulfonic acid group in 2-acrylamide-2-methylpropanesulfonic acid, and the ionized sulfonic acid radical can affect the hydration of the hydroxyl group in the polyvinyl alcohol molecular chain, resulting in the aggregation and crystallization of the polyvinyl alcohol polymer. The present invention uses the Hofmeister effect in the double network structure to induce hydrogel crystallization.

[0061] The prepared pre-gel can be further improved in mechanical properties of the hydrogel by salting out, and can be endowed with antifreeze and anti-swelling properties.

[0062] The present invention also provides a hydrogel prepared by the preparation method according to the above technical solution, wherein the tensile strength of the hydrogel is 1.2-1.44 MPa, and may be 1.31-1.42 MPa; the elongation at break of the hydrogel is 386.49-403.8%, and may be 393.18-401.24%; the toughness of the hydrogel is 2.09-2.79 MJ / m 3 , which can be 2.46~2.77MJ / m 3; The Young's modulus of the hydrogel is 0.29 to 0.36 MPa, and may be 0.33 to 0.36 MPa; The swelling rate of the hydrogel after immersion in water for 7 days is 11.67 to 17.87%, and may be 11.74 to 16.18%.

[0063] The hydrogel prepared according to the preparation method provided by the present invention has a double network structure, high strength and toughness, good freezing resistance and good swelling resistance.

[0064] The present invention also provides the application of the hydrogel described in the above technical solution as a medical material. As a specific embodiment of the present invention, the hydrogel can be used as a raw material to prepare a flexible sensor; the flexible sensor can be suitable for wearing on various parts of the human body to monitor various parts of the human body.

[0065] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0066] Example 1

[0067] Stir 1 g of polyvinyl alcohol and 9 mL of deionized water at 100 °C for 50 min to obtain a polyvinyl alcohol aqueous solution;

[0068] Stir 0.4 g of sodium hydroxide in 1 mL of deionized water at room temperature 25°C for 5 min to obtain a sodium hydroxide solution;

[0069] Dissolve 1.6 g of 2-acrylamide-2-methylpropanesulfonic acid in a polyvinyl alcohol aqueous solution at 60° C. under stirring for 5 min to obtain a first mixed solution;

[0070] The first mixed solution and the sodium hydroxide solution were stirred and mixed at 60° C. for 1 hour to obtain a second mixed solution;

[0071] The second mixed solution, 0.048 g of polyethylene glycol diacrylate, and 0.0157 g of 1-hydroxycyclohexyl phenyl ketone were mechanically stirred at 60° C. for 0.5 h, and then photocrosslinked for 40 min by ultraviolet light initiation to obtain a pregel;

[0072] The pregel was subjected to two cycles of freeze-thaw (the single freezing temperature was -20°C and the single freezing time was 12 h; the single thawing temperature was 10°C and the single thawing time was 12 h), then immersed in 500 mL of deionized water for 12 h, and finally immersed in 300 mL of 2 mol / L sodium chloride solution for 12 h for salting out to obtain a hydrogel, recorded as P(PNa)N-2.

[0073] Example 2

[0074] The hydrogel was prepared according to the method of Example 1, except that the molar concentration of the sodium chloride solution used for salting out was 3 mol / L. The obtained hydrogel was recorded as P(PNa)N-3.

[0075] Example 3

[0076] The hydrogel was prepared according to the method of Example 1, except that the molar concentration of the sodium chloride solution used for salting out was 4 mol / L. The obtained hydrogel was recorded as P(PNa)N-4.

[0077] Example 4

[0078] The hydrogel was prepared according to the method of Example 1, except that the molar concentration of the sodium chloride solution used for salting out was 5 mol / L. The obtained hydrogel was recorded as P(PNa)N-5.

[0079] Comparative Example 1

[0080] The hydrogel was prepared according to the method of Example 1, except that the salting-out step of immersing in sodium chloride solution was omitted, and the immersion time in water was extended to 24 h. The obtained hydrogel was recorded as P(PNa)N-0.

[0081] Comparative Example 2

[0082] A hydrogel was prepared according to the method of Example 1, except that the step of mixing the first mixed solution and the sodium hydroxide solution was omitted, and the steps of soaking in water and soaking in a sodium chloride solution for salting out were also omitted. The obtained hydrogel was recorded as PP.

[0083] Comparative Example 3

[0084] The hydrogel was prepared according to the method of Example 1, except that the step of soaking in water and the step of salting out in sodium chloride solution were omitted. The obtained hydrogel was recorded as P(PNa).

[0085] Experimental test methods

[0086] 1. X-ray diffraction analysis

[0087] The crystal structure of the sample was characterized by an X-ray diffractometer (XRD, D8Advance) from Bruker, Germany. The ray source was Cu-Ka The hydrogels prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were scanned under the test conditions of 25 mA and 40 kV to obtain XRD spectra as shown in Figure 2 shown.

[0088] Depend on Figure 2It can be seen that the crystallization peak of the hydrogel is significantly enhanced after salting-out treatment, indicating that the crystallization performance of the hydrogel can be improved by salting-out treatment. The reason is that salting-out will affect the hydration of hydroxyl groups on the polymer molecular chain, causing the aggregation of polyvinyl alcohol molecular chains, which is conducive to crystallization.

[0089] 2. Mechanical properties test

[0090] According to the national standard (GB1040-92), the tensile properties of the hydrogels prepared in Examples 1 to 4 and Comparative Example 1 were tested using a HZ-1007E universal material testing machine produced by Dongguan Lixian Instrument Technology Co., Ltd. The sample shape was dumbbell-shaped strips (2×14 mm 2 ), stretching speed 50mm / min, and the results are listed in Table 1.

[0091] Table 1 Mechanical properties of hydrogels of Examples 1 to 4 and Comparative Example 1

[0092]

[0093] It can be seen from the results in Table 1 that after salting out, the mechanical properties of the hydrogel are significantly improved. This is because the penetration of the salt solution into the hydrogel will affect the interaction between the molecular chains of polyvinyl alcohol, causing the molecular chains to aggregate and crystallize, ultimately increasing the dissipated energy of the hydrogel and thus improving the mechanical properties.

[0094] 3. Swelling performance test

[0095] The hydrogels prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were immersed in deionized water for one week, during which the swelling rate was calculated according to the mass change of the hydrogel to evaluate the swelling performance of the hydrogel. Figure 3 The swelling pictures of the hydrogels prepared in Example 3, Comparative Example 2 and Comparative Example 3 are shown in Table 2.

[0096] Table 2 Swelling rate of hydrogels of Examples 1 to 4 and Comparative Examples 1 to 3

[0097]

[0098]

[0099] Note: In Table 2, × indicates that the hydrogel has been destroyed.

[0100] From the results in Table 2, it can be seen that the addition of sodium hydroxide solution can protect the integrity of the hydrogel and improve its anti-swelling performance. After salting out, the anti-swelling performance of the hydrogel is further improved. This is mainly attributed to the fact that the ionized sulfonic acid groups affect the interaction between the polyvinyl alcohol molecular chain and water, causing the molecular chain to aggregate and crystallize. Finally, the crystallization performance is further improved by salting out.

[0101] 4. Antifreeze performance test

[0102] The hydrogels were placed in a -20°C refrigerator for 24 h and at room temperature 20°C for 24 h for shape comparison.

[0103] Figure 4 The following are the actual pictures of the hydrogels of Examples 1 to 4 and Comparative Examples 1 to 3 at different temperatures. Figure 4 It can be seen that at room temperature 20°C, the hydrogels of Examples 1 to 4 and Comparative Examples 1 to 3 are all soft and droop naturally. However, at -20°C, after freezing for 24 hours, Comparative Examples 1 to 3 are all frozen and hardened, while Examples 1 to 4 remain soft. This indicates that the hydrogels treated with high-concentration salt solution can greatly improve their antifreeze properties. The reason is that the salt solution penetrates into the interior of the hydrogel, and the sodium ions and chloride ions affect the interaction of water molecules and lower the freezing point of water.

[0104] 5. ECG monitoring performance test

[0105] Purchase an ECG acquisition module ADS1292R and commercial medical electrode sheets. After connecting the electrode sheets to the acquisition module, attach them to the left and right wrists and lower abdomen of the human body, respectively, to perform ECG monitoring. When using Example 3 for ECG acquisition, the gel electrode on the original commercial electrode sheet is removed, and the hydrogel of Example 3 is attached to perform ECG monitoring.

[0106] Figure 5 The results of human ECG monitoring using Example 3 and commercial gel electrodes are as follows: Figure 5 It can be seen that Example 3 can monitor the human electrocardiogram curve and distinguish different electrocardiogram waveforms just like the commercial gel electrode.

[0107] The actual picture of Example 3 and the commercial gel electrode after being immersed in water for 3 hours is as follows Figure 6 As shown, the electrodes of Example 3 after being soaked in water are used to continue ECG monitoring, and the results are shown in FIG. Figure 7 shown.

[0108] according to Figure 6 and Figure 7 It can be seen that the shape of the electrode of Example 3 does not undergo significant deformation after being soaked in water, indicating that it has good anti-swelling performance; after the electrode of Example 3 is soaked in water, an obvious electrocardiogram curve can still be monitored.

[0109] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a hydrogel, characterized in that: The following steps are involved: Mixing polyvinyl alcohol, 2-acrylamide-2-methylpropane sulfonic acid, a strong base, a photoinitiator, a crosslinking agent and water, and performing photocrosslinking to obtain a pregel; The pregel is freeze-thawed cyclically and then salted out to obtain the hydrogel.

2. The method for preparing the hydrogel according to claim 1, characterized in that: The mixing comprises the following steps: first mixing the polyvinyl alcohol and a portion of water to obtain a polyvinyl alcohol aqueous solution; First dissolving a strong base in the remaining portion of water to obtain a strong base solution; dissolving the 2-acrylamide-2-methylpropanesulfonic acid in the polyvinyl alcohol aqueous solution to obtain a first mixed solution; The first mixed solution and the strong base solution are mixed for a second time to obtain a second mixed solution; The second mixed solution, the photoinitiator and the cross-linking agent are mixed for the third time.

3. The method for preparing the hydrogel according to claim 2, characterized in that: The mass ratio of the polyvinyl alcohol to part of the water is 1:8-9; the temperature of the first mixing is 95-105° C., and the time of the first mixing is 40-60 min; The strong base includes sodium hydroxide or potassium hydroxide; the mass ratio of the strong base to the remaining water is 2:4-7; The mass ratio of the polyvinyl alcohol aqueous solution to 2-acrylamide-2-methylpropane sulfonic acid is 5:0.6-0.9; the temperature of the second dissolution is 60-65° C., the second dissolution is carried out under stirring, and the stirring time is 5-10 minutes; The mass ratio of polyvinyl alcohol to strong base in the second mixed solution is 1:0.4-0.

7.

4. The method for preparing the hydrogel according to claim 1, characterized in that: The photoinitiator includes 1-hydroxycyclohexyl phenyl ketone; the crosslinking agent includes polyethylene glycol diacrylate; The mass ratio of the 2-acrylamide-2-methylpropanesulfonic acid, the photoinitiator and the crosslinking agent is 1.6: 0.015-0.016: 0.048-0.060; The temperature of the third mixing is 60-65° C., the third mixing is performed under stirring, and the stirring time is 30-40 minutes.

5. The method for preparing the hydrogel according to claim 1, characterized in that: The light used for the photo-crosslinking is ultraviolet light; the time for the photo-crosslinking is 35 to 45 minutes.

6. The method for preparing the hydrogel according to claim 1, characterized in that: The cyclic freeze-thaw process is a process of cyclic freezing and thawing, wherein the time for a single freezing is 11 to 13 hours, the time for a single thawing is 11 to 13 hours, and the number of cycles is 2 to 3 times.

7. The method for preparing the hydrogel according to claim 1, characterized in that: Before the salting out, the method further comprises: soaking the product after the freeze-thaw cycle in water for 11 to 13 hours; The salting out is to soak the product after soaking in water in an inorganic salt solution; The inorganic salt solution includes sodium chloride solution, magnesium chloride solution, calcium chloride solution or potassium chloride solution; The molar concentration of the inorganic salt aqueous solution is 2 to 5 mol / L; The soaking time in the inorganic salt solution is 11 to 13 hours.

8. The hydrogel prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The hydrogel has a tensile strength of 1.2-1.44 MPa, an elongation at break of 386.49-403.8%, and a toughness of 2.09-2.79 MJ / m 3 , Young's modulus is 0.29-0.36 MPa; the swelling rate of the hydrogel after being immersed in water for 7 days is 11.67-17.87%.

9. Use of the hydrogel according to claim 8 as a medical material.

10. The use according to claim 9, characterized in that: The hydrogel is used as a raw material to prepare a flexible sensor.

Citation Information

Cited By

  • Dielectric near-zero polymer hydrogel, preparation method thereof and flexible capacitive sensor

    CN121319276A

  • Dielectric near-zero polymer hydrogel, preparation method thereof and flexible capacitive sensor

    CN121319276B